2009
DOI: 10.2337/db09-0655
|View full text |Cite
|
Sign up to set email alerts
|

Nephrin Is Expressed on the Surface of Insulin Vesicles and Facilitates Glucose-Stimulated Insulin Release

Abstract: OBJECTIVENephrin, an immunoglobulin-like protein essential for the function of the glomerular podocyte and regulated in diabetic nephropathy, is also expressed in pancreatic β-cells, where its function remains unknown. The aim of this study was to investigate whether diabetes modulates nephrin expression in human pancreatic islets and to explore the role of nephrin in β-cell function.RESEARCH DESIGN AND METHODSNephrin expression in human pancreas and in MIN6 insulinoma cells was studied by Western blot, PCR, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 48 publications
(62 reference statements)
2
51
0
Order By: Relevance
“…However, by contrast, the additional phosphorylation of Tyr-1217 promoted nephrin degradation (10). Nephrin is found both on the plasma membrane and on insulin vesicles in b-cells (8), and it regulates insulin exocytosis through interaction with the actin cytoskeleton and phosphorylation-dependent trafficking (10). In the current study, we found that IP receptor agonism phosphorylated nephrin at Tyr-1176/1193 in podocytes and in MIN6 cells.…”
Section: Discussionmentioning
confidence: 46%
See 4 more Smart Citations
“…However, by contrast, the additional phosphorylation of Tyr-1217 promoted nephrin degradation (10). Nephrin is found both on the plasma membrane and on insulin vesicles in b-cells (8), and it regulates insulin exocytosis through interaction with the actin cytoskeleton and phosphorylation-dependent trafficking (10). In the current study, we found that IP receptor agonism phosphorylated nephrin at Tyr-1176/1193 in podocytes and in MIN6 cells.…”
Section: Discussionmentioning
confidence: 46%
“…Although preservation of islet b-cell mass may explain some of the reduction in blood glucose levels with selexipag treatment in STZ-C57BL/6 mice, a separate secretagogue-like effect is supported by the findings in MIN6 cells. However, unlike secretagogue therapies currently available in the clinic, IP receptor agonism alone is not sufficient to induce insulin release, emphasizing that its effects occur downstream of glucose-sensing, plausibly by priming b-cells through nephrin phosphorylation (8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations